2021
DOI: 10.3390/mi12111324
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced HIFU Theranostics with Dual-Frequency-Ring Focused Ultrasound and Activatable Perfluoropentane-Loaded Polymer Nanoparticles

Abstract: High-intensity focused ultrasound (HIFU) has been widely used in tumor ablation in clinical settings. Meanwhile, there is great potential to increase the therapeutic efficiency of temporary cavitation due to enhanced thermal effects and combined mechanical effects from nonlinear vibration and collapse of the microbubbles. In this study, dual-frequency (1.1 and 5 MHz) HIFU was used to produce acoustic droplet vaporization (ADV) microbubbles from activatable perfluoropentane-loaded polymer nanoparticles (PFP@Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…1 illustrates the dual-frequency focused ultrasound system used for the PFP nanodroplets ADV nucleation simulation. The ultrasound transducer consisted of two confocal spherical annular elements, which had a similar geometry as used in previous experimental studies [32] , [33] . The inner ring had a radius r 1 (25 mm) and was stimulated at a high frequency, while the outer ring had a radius r 2 (47 mm) and was stimulated at a lower frequency.…”
Section: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 illustrates the dual-frequency focused ultrasound system used for the PFP nanodroplets ADV nucleation simulation. The ultrasound transducer consisted of two confocal spherical annular elements, which had a similar geometry as used in previous experimental studies [32] , [33] . The inner ring had a radius r 1 (25 mm) and was stimulated at a high frequency, while the outer ring had a radius r 2 (47 mm) and was stimulated at a lower frequency.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…This was shown to reduce the ADV threshold, manipulate the ADV volume and increase the cavitation efficacy [32] . The dual-frequency HIFU was also shown to effectively activate the phase transition of perfluoropentane (PFP) nanoparticles into microbubbles, while significantly reducing the HIFU threshold for thermal ablation lesion in phantoms, enhancing the antitumor efficacy, and realizing ultrasound monitoring imaging in vitro and in vivo [33] . It indicated a short pulsed high-frequency ultrasound was the main source for ADV, and the long pulsed low-frequency ultrasound increased cavitation-induced bioeffects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been indicated that the adoption of NPs can effectively change the acoustic environment (tissue structure, density, blood supply and functional state on ultrasonic transmission and energy deposition during HIFU treatment) of tumour tissues (30), making them more sensitive to HIFU, resulting in greater ablative efficacy with the same or lower HIFU irradiation doses. Additionally, since the first report on the combination of HIFU with nanotechnology in 2000 (31), it has been recognized that HIFU induces target drug release from platforms such as NPs and liposomes to enhance the ablative efficacy of HIFU and improve safety (32); since then, studies have attempted to design nanomedicines to improve the efficacy of HIFU (33)(34)(35)(36) however, progress has not seen clinical translation. Additionally, the promotion of theranostics also highlights novel opportunities in this field.…”
Section: Nanomedicines For High-intensity Focused Ultrasound Cancer T...mentioning
confidence: 99%
“…The incorporation of PFP also allows ultrasound monitoring of the whole procedure, making these nanodroplets another promising HIFU-based theranostic candidate. On the other hand, Chen et al ( 35 ) focused on HIFU and synthesized PFP-loaded polymer NPs (PFP@Polymer NPs) that were responsive to a dual-frequency HIFU pattern. Compared with single-frequency HIIFU, PFP@Polymer NPs under the irradiation of dual-frequency HIFU (1.1 and 5.0 MHz) were reported to significantly decrease the acoustic intensity threshold needed for ablation from 216.86 to 62.38 W/cm 2 , thus effectively decreasing collateral damage.…”
Section: Nano-based Hifu Cancer Theranosticsmentioning
confidence: 99%
“…To respond to the thermal effects of FUS, the particles that carry small-molecule agents to the specific sites are designed to be temperature-sensitive, with a certain heat or energy threshold for the drug to be released ( Dromi et al, 2007 ; Luo et al, 2017 ). Futhermore, the particles can act as additional nucleation sites and reduce the cavitation threshold during microbubble (MB) formation, which enhances the mechanical effects of FUS and increases drug unloading through acoustic manipulation at the specific positions ( Airan et al, 2017 ; Khirallah et al, 2019 ; Chen et al, 2021 ). These particles can be either organic, such as lipid- or polymer-based, or inorganic, for example, metallic, or a combination of both types ( Mai et al, 2021 ).…”
Section: Focused Ultrasound Technologymentioning
confidence: 99%